Neutron activation analysis of plantinum converter and furnace mattes using a D-T sealed tube neutron generator - Majawa, Louis John (Department of Physics, 2014)
Neutron activation analysis (NAA) has been applied to furnace matte and converter matte samples with the objective of studying the natural variation in the elemental composition of the samples, with a view to characterize the samples for their source of origin. The experimental work was carried out at iThemba LABS national laboratory near Cape Town, South Africa. A new NAA facility was designed and built for this purpose, and fully characterized, featuring a 14 MeV neutron generator. Gamma-ray spectra were measured using an HPGe detector. A number of isotopes were identified in the measured spectra and the elemental concentrations calculated. Radiometric spectral measurements were also made of the samples, without prior irradiation, and the spectra analysed for isotopic variation. Consequences for sample identification via these techniques are discussed.